2000
DOI: 10.1111/j.1349-7006.2000.tb00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Receptor and Retinoid × Receptor in Ductal Carcinoma in situ and Intraductal Proliferative Lesions of the Human Breast

Abstract: Retinoic acid (RAR) and retinoid X receptors (RXR) are essential in the transcriptional actions of retinoids. To date, RAR and RXR have not been examined in precancerous lesions and/or ductal carcinoma in situ (DCIS) in human breast. Therefore, we examined RAR and RXR subtypes in DCIS (58 cases), atypical ductal hyperplasia (ADH) (32 cases), and proliferative disease without atypia (PDWA) (32 cases) to study the status of these RARs and RXRs. Immunoreactivities for RAR α α α α, RXR α α α α, RXR β β β β, and RX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
2
28
1
Order By: Relevance
“…They bind to homo-or heterodimers of the retinoic acid (RAR) or retinoid X (RXR) receptor families, as well as other proteins, and the concentrations of these components influence the retinoid response [34,35]. For instance, higher levels of the RARalpha are associated with greater proliferation rates of ER 1 ductal carcinoma in situ breast cancer [36]. Retinoid receptors influence a diverse range of proteins involved in signal transduction and cell cycle control, and make direct protein interaction with various kinases and transcription factors [34].…”
Section: Breast Cancer Resultsmentioning
confidence: 99%
“…They bind to homo-or heterodimers of the retinoic acid (RAR) or retinoid X (RXR) receptor families, as well as other proteins, and the concentrations of these components influence the retinoid response [34,35]. For instance, higher levels of the RARalpha are associated with greater proliferation rates of ER 1 ductal carcinoma in situ breast cancer [36]. Retinoid receptors influence a diverse range of proteins involved in signal transduction and cell cycle control, and make direct protein interaction with various kinases and transcription factors [34].…”
Section: Breast Cancer Resultsmentioning
confidence: 99%
“…Mu et al [36] reported that the combined treatment of two types of retinoids, TTNPB for RAR and LG100268 for RXR synergistically stimulate aromatase enzymatic activity in MCF-7. These nuclear receptors such as ERR␣, RAR, and RXR were all detected in parenchymal carcinoma cells but not in stromal nor in normal epithelial cells of breast carcinoma tissues [37][38][39]. In RT-PCR analysis of aromatase (Fig.…”
Section: Aromatase In Human Breast Carcinoma Cell Linesmentioning
confidence: 95%
“…However, we did not detect either SXR mRNA or protein in normal human breast tissues. We reported previously that the obligate SXR heterodimeric partner, retinoid X receptor, was only very weakly expressed in normal breast cells (36,37). SXR was also detected in hormone-dependent endometrial carcinoma cell but not in normal endometrium (13).…”
Section: Discussionmentioning
confidence: 99%